(untitled) (Analysis in Theory and Applications, 2017)
In this paper, we establish the L^p(R^n+1 ) boundedness for the commutators of singular integrals associated to surfaces of revolution, {(t,φ(|t|)):tR^n}, with rough kernels ΩL(L)^2(S^n-1), if φ(|t|)=|t|.